The Effect of Cash Flows on Firm Performance: A Research on BIST - İbrahim Kaya; Hakan Özçelik (İstanbul İktisat Dergisi)
In line with the development and change in the financial markets, the cash flow statement has become an important financial statement, and the strategic value of cash flow information for company managers and investors has increased. In this study; it is aimed to measure the effect of cash flow information on firm performance. Within the scope of the purpose, data of 57 companies operating in manufacturing and non-manufacturing sectors, excluding financial institutions, from BIST 100 companies covering the period of 2014 - 2019 were used. In the model developed in the study, cash flow statement data was used as the independent variable, while the return on assets ratio (ROA), return on equity ratio (ROE) and Tobin q ratio were selected as dependent variables. As a result of the study, it was determined that cash flows influence business performance. The statistically significant positive relationships between cash flows from operating activities and ROA, cash flows from financing activities and ROE, and dividend payments and Tobin’s q ratio with end-of-period cash balance were identified as the prominent results of the study.